Ecology of the bushpig Potamochoerus porcus Linn. 1758 in the Cape Province, South Africa - Seydack, Armin H. W. (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD) -- Stellenbosch University, 1990.